The Influence of Concrete Strength on Shear Capacity of Reinforced Concrete Members without Shear Reinforcement - Słowik, Marta (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
In the paper, dimensioning rules for shear capacity in reinforced concrete members without shear reinforcement given in Eurocode 2, ACI Standard 318 and Model Code 2010 are described. The fib Model Code recommendations are described in more detailed way as they are based on a new concept. The shear strength calculated on the basis of the mentioned codes is later compared to the results of test from professional literature in order to verify standard methods and to analyze the influence of concrete strength on shear capacity in beams without stirrups.